الأداء المهني للأستاذ الجامعي في نظام اللمدي - بواب, رضوان; ميلاط, صبرينة (جامعة الوادي - University of Eloued, 2021)
ملخص: إن الإصلاحات التي عرفها نظام التعليم الجامعي بتغيير النظام القديم ( الكلاسيكي ) بالنظام الجديد (ل.م.د) وتعميمه على مستوى الجامعات جاء من أجل إحداث تكافؤ في مستوى التعليم بين الدول المعتمد لهذا النظام من جهة، ومن أجل تحسين المردود التربوي والتعليمي من جهة أخرى، حيث يتم من خلاله تحقيق توافق بين إمكانيات الفرد، وقدراته، وطموحاته وإمكانية تجسيدها على المستوى المهني ،بغية التماشي مع التطورات العالمية. ونجاح هذا النظام لم يعد مقتصرا على عملية التغيير فقط ، بل كان للأستاذ الجامعي دور فعال في إنجاح العملية التعليمية لهذا النظام من خلال الجهود المبذولة في مختلف السياقات التربوية، هذه الجهود والآليات تعد مطلبا ضروريا لتحديث وتطوير أنظمة التعليم الجامعي وتحسين نوعيته إضافة إلى تطوير مستوى الأداء والكفاءة عند أعضاء هيئة التدريس الجامعي، انطلاقا من ارتباط جودة وتطور أداء الأستاذ الجامعي وبجودة التعليم الجامعي ومن ثمة تحقيق الإبداع والتميز في أداء الجامعة بصفة عامة. The educational system at the level of the university has experienced many reforms. The replacement on one side of the old system (classical) by the new one (L.M.D) throughout universities comes for the sake of equalizing education all over the countries following this system. On the other side, it comes for the improvement of the instructional and educational product, to achieve accordance between the individual’s capacities and ambitions, and the ability to apply it on the professional level in order to cope with current developments all over the world. These changes are not the only reason for the system to be successful, but rather the university plays an effective role for the learning process to be successful as well his effects are very important condition for the betterment of the university educational system and its quality, as well as the improvement of faculty members competence and performance starting from the relation between the quality and the improvement of university teacher’s performance and the quality of university education then the establishment of creativity in the university performance in general.
محددات المهنة وسبل تحسينها
مقال
Keywords: الجامعة-الاستاذ الجامعي-الاداء المهني,نظام اللمدي; university professor, university, performance, LMD system